Amniotic fluid glucose level in PPROM pregnancies: a glance at the old friend. (18th June 2022) - Kacerovsky, Marian; Holeckova, Magdalena; Stepan, Martin; Gregor, Miroslav; Vescicik, Peter; Lesko, Daniel; Burckova, Hana; Pliskova, Lenka; Bolehovska, Radka; Andrys, Ctirad; Jacobsson, Bo; Musilova, Ivana
Abstract: Introduction: To determine the amniotic fluid glucose levels in pregnancies complicated by preterm prelabor rupture of membranes (PPROM) based on the presence of microbial invasion of the amniotic cavity and/or intra-amniotic inflammation. Methods of Study: A total of 142 women with singleton pregnancies complicated by PPROM between gestational ages 24 + 0 and 36 + 6 weeks were included. Amniocentesis was performed at the time of admission. The assessments of microbial invasion of the amniotic cavity (using both cultivation and non-cultivation techniques) and intra-amniotic inflammation (amniotic fluid interleukin-6 levels ≥ 3000 pg/mL) were performed on all the women. Based on the presence of microbial invasion of the amniotic cavity and/or intra-amniotic inflammation, the women were further categorized into the subgroups: (i) intra-amniotic infection (the presence of both microbial invasion of the amniotic cavity and intra-amniotic inflammation); (ii) sterile intra-amniotic inflammation (the presence of intra-amniotic inflammation without microbial invasion of the amniotic cavity); (iii) colonization (the presence of microbial invasion of the amniotic cavity without intra-amniotic inflammation); and (iv) negative amniotic fluid (the absence of either microbial invasion of the amniotic cavity or intra-amniotic inflammation). Amniotic fluid glucose levels were assessed using enzymatic reference method with hexokinase. Results: There was a difference in the amniotic fluid glucose levels among the women with intra-amniotic infection, sterile intra-amniotic inflammation, colonization, and those with negative amniotic fluid ( p  < .0001). No difference was found in the amniotic fluid glucose levels between women with intra-amniotic infection and those with sterile intra-amniotic inflammation [infection: median 11.6 mg/dL (0.7 mmol/L) vs. sterile: median 6.3 mg/dL (0.4 mmol/L); p  = .41] and between women with colonization and negative amniotic fluid [colonization: median 21.6 mg/dL (1.2 mmol/L) vs. negative: median 23.4 mg/dL (1.3 mmol/L; p  = .67]. Women with intra-amniotic infection and sterile intra-amniotic inflammation had lower amniotic fluid glucose levels than women with colonization and with negative amniotic fluid in crude analysis as well as after adjustment for gestational age at sampling. Amniotic fluid glucose level of 10 mg/dL (0.56 mmol/L) was the optimal concentration for the identification of intra-amniotic inflammation in women with PPROM. Conclusions: The presence of intra-amniotic inflammation was associated with lower amniotic fluid glucose levels in singleton pregnancies complicated with PPROM. An amniotic fluid glucose level of 10 mg/dL (0.56 mmol/L) was the optimal concentration for the identification of intra-amniotic inflammation in PPROM pregnancies. In the absence of better amniotic fluid markers, amniotic glucose could be used as a marker of intra-amniotic inflammation, with very good specificity in PPROM pregnancies.